Importance of Employee Participation in Lean Thinking and Their Competency Towards Employee Innovative Behaviour - Hamid, Roshayati binti Abdul; Ismail, Md Daud bin; Ismail, Ida Rosnita binti (UI Scholars Hub, 2020)
Research Aims: The process of innovation is complex and involved various stage which required employees to have an innovative behaviour. Underpinned by social exchange theory, this study examines how employee participation in Lean Thinking influence the employees' innovative behaviour. We also examine the possibility that competency moderates this relationship. Design/methodology/approach: Measurements from previous studies were adapted in developing the questionnaire and data were analysed using the Partial Least Squares (PLS) approach. Research Findings: The results showed that there is a positive relationship between employee participation in Lean Thinking and employee innovative behaviour, and a positive relationship between employee competency and employee innovative behaviour. However, employee competency does not moderate the relationship between employee participation in Lean Thinking and employee innovative behaviour. Theoretical Contribution/Originality: This study enhanced the social exchange theory by proving that employees are motivated to perform more than their duties and results into innovative behaviour when they are encouraging to participate in Lean Thinking. Managerial Implication in the South East Asian context: Managers should keep encouraging employee to participate in Lean Thinking and give empowerment for decision making which could engender employee innovative behaviour. Research limitation & implications: The main limitation is the insignificant moderating effect of employee competency. Therefore, we recommend that researchers use psychological variables such as psychological empowerment and psychological ownership.